1982
DOI: 10.1002/hep.1840020616
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of albumin receptors onisolated human hepatocytes by light and scanning electron microscopy

Abstract: The presence of albumin receptors on the plasma membrane of isolated human hepatocytes was investigated employing albumin-coupled latex minibeads. Hepatocyte-latex reaction was visualized by phase contrast and scanning electron microscopy.The experiments demonstrate that hepatocytes exhibit binding activity for polymeric and monomeric forms of glutaraldehyde-treated albumin. Additionally, the reaction was shown to be speciesnonspecific.These findings support the hypothesis that polymerized albumin may act as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

1984
1984
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(27 citation statements)
references
References 11 publications
0
26
1
Order By: Relevance
“…Similar receptors have been identified on the surface membrane of hepatocytes (Lenkei et al, 1977;Trevisan et al, 1982) and it has been suggested that these receptors could be important in HBV infection by facilitating entry of the virus into the hepatocyte. Antibodies which react with the pHSA receptor may then be important in virus neutralization.…”
Section: Introductionmentioning
confidence: 60%
“…Similar receptors have been identified on the surface membrane of hepatocytes (Lenkei et al, 1977;Trevisan et al, 1982) and it has been suggested that these receptors could be important in HBV infection by facilitating entry of the virus into the hepatocyte. Antibodies which react with the pHSA receptor may then be important in virus neutralization.…”
Section: Introductionmentioning
confidence: 60%
“…This sequence is responsible for the receptor for polymerized human as well as chimpanzee albumins carried by HBV (24,37,45). Since hepatocytes also have the receptor for polymerized albumin that is not species-specific but is organ-specific (46,47), HBV would be able to gain access to them via albumin polymers that occur in the circulation as the result of molecular aging. Should such a mechanism be operating in the presumed hepatotropism of HBV, antibodies to the receptor would naturally be expected to neutralize HBV by blocking the very site required for its entry into hepatocytes.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, antibody-dependent enhancement of infection mediated by interactions between the Fc region of virus-specific immunoglobulin G and Fc receptors on certain cells has been described for a number of viruses (29). There have only been a few reports indicating that other components serve as a bridge between viruses and target cells: (i) C4BP and coagulation factor IX have been reported to promote Ad5 interactions with target cells when the CAR binding site of the Ad5 fiber has been ablated (39); (ii) dipalmitoyl phosphatidylcholine may be involved in Ad2 entry into alveolar epithelial cells (5); (iii) polymerized human serum albumin is necessary and sufficient for binding of hepatitis B virus-like particles to human liver plasma membranes (32,44); (iv) BLf has been suggested to enhance infection of gC-negative herpes simplex viruses in mouse fibroblasts (24); and (v) HLf has been proposed to generate formation of an HHV8-lactoferrin-glycosaminoglycan-epithelial cell receptor complex, which may increase the initial infective viral dose in the vicinity of potential target cells and increase the risk of infection (20). This report further potentiates the role of lactoferrin as a soluble component with the ability to promote binding to and infection of target cells, by serving as a bridge between the virion and the surface of the target cell.…”
Section: Discussionmentioning
confidence: 99%